Implikasi Putusan Uji Materi Mahkamah Agung terhadap Kedudukan Pemilihan Presiden dan Wakil Presiden Tahun 2019 dan 2024 - Khosnol Khotimah (Ma’mal: Jurnal Laboratorium Syariah dan Hukum, 2021)
Abstract: This study aims to find out how the implications of the Supreme Court's Decision No. 44 P/Hum/2019 on the position of the presidential and vice-presidential elections in 2019 and 2024. This research is normative juridical research that examines Law no. 7 of 2017 concerning General Elections and Law no. 42 of 2008 concern the General Election of President and Vice President. In addition, the author also uses the Constitutional Court Decision No. 50/PUU-XII/2014 and Supreme Court Decision No. 44 P/Hum/2019 as a form of different decisions that result in different views regarding the determination of the results of the 2019 presidential and vice-presidential elections. The conclusion of this study is Supreme Court Decision No. 44/P/Hum/2019 has no implications for the elected pairs of presidential and vice-presidential candidates. The elected president is still declared valid in the first round of voting even though there are differences between the Supreme Court's decisions and the Constitutional Court because the findings of the Constitutional Court are final and binding. The suggestions from this research are, first, to make a clear separation between the authority of the Constitutional Court and the Supreme Court so that the main functions of the court of justice and the court of law are precise. Second, revise Law Number 7 of 2017 concerning General Elections related to the number of votes to determine the elected presidential and vice-presidential candidates. Keywords: Constitutional Court, Supreme Court, Judicial Review, General Election.   Abstrak: Penelitian ini bertujuan untuk menganalisis implikasi Putusan Mahkamah Agung No. 44 P/Hum/2019 terhadap kedudukan pemilihan Presiden dan Wakil Presiden Tahun 2019 dan 2024. Penelitian ini adalah penelitian yuridis normatif yang mengkaji Undang-undang No. 7 tahun 2017 tentang Pemilihan Umum dan Undang-undang No. 42 tahun 2008 tentang Pemilihan Umum Presiden dan Wakil Presiden. Selain itu, penulis juga menggunakan Putusan Mahkamah Konstitusi No. 50/PUU-XII/2014 dan Putusan Mahkamah Agung No. 44 P/Hum/2019 sebagai bentuk perbedaan putusan yang berakibat pada perbedaan pandangan terkait penetapan hasil pemilihan presiden dan wakil presiden terpilih 2019.  Kesimpulan dari penelitian ini adalah Putusan Mahkamah Agung No. 44/P/Hum/2019 tidak berimplikasi terhadap pasangan terpilih calon presiden dan wakil presiden 2019. Presiden terpilih tetap dinyatakan sah pada pemilihan suara putaran pertama sekalipun terdapat perbedaan antara putusan Mahkamah Agung dan juga Mahkamah Konstitusi, dikarenakan putusan Mahkamah Konstitusi yang bersifat final and binding. Saran dari penelitian ini yaitu pertama, melakukan pemisahan yang jelas antara kewenangan Mahkamah Konstitusi dan Mahkamah Agung, sehingga jelas tupoksi antara court of justice dan court of law. Kedua, melakukan revisi terhadap Undang-Undang Nomor 7 Tahun 2017 Tentang Pemilihan Umum terkait jumlah suara penetapan calon presiden dan wakil presiden terpilih. Kata Kunci: Mahkamah Konstitusi, Mahkamah Agung, Judicial Review¸ Pemilihan Umum.